Bandongan Method in Tarjamah Learning in Nururrahmah Assembly Medan, North Sumatera - Gajah, Azizah Sabrina; Khoirul Jamil (Ukazh : Journal of Arabic Studies, 2025)
This study aims to examine the implementation of the bandongan method in tarjamah (translation) learning at Majelis Nururrahmah in Medan, North Sumatra. Tarjamah learning plays an important role in understanding Arabic religious texts, especially in non-formal educational settings such as majelis taklim. The bandongan method used focuses on direct reading and explanation of texts by the ustadzah (female teacher) to the congregation. This study employs a qualitative approach using participatory observation, in-depth interviews, and documentation techniques. The results show that this method can enhance the congregation’s understanding of classical Arabic texts, particularly through the study of Nashoihud Diniyah and Syarah Ainiyah. Although it is one-directional and lacks active participation, the repetition of material and contextual explanations reinforce comprehension of the meaning and structure of the texts. The uniqueness of this study lies in the application of the bandongan method in Arabic language learning within a non-formal environmentan area that has rarely been scientifically examined. The findings indicate that the bandongan method has the potential to become an alternative strategy in implementing tarjamah learning in non-formal educational institutions.